1995
DOI: 10.1007/bf00164025
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary relationships of two families of cottoid fishes of Lake Baikal (East Siberia) as suggested by analysis of mitochondrial DNA

Abstract: Fragments of mtDNA genes Cyt B, ATPase 6, and ATPase 8 of six cottoid fishes species of Lake Baikal (East Siberia) were amplified and sequenced. In addition mtDNAs of the same fish were subjected to restriction analysis. The data obtained were used to construct phylogenetic trees. The topology of the ATPase tree differs from those of the Res (restriction) and Cyt B trees. Clustering of species within the trees confirms the viewpoint of Taliev (1955, Baicalian Sculpins (Cottoidei)) according to which Baikalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In cottoid fish of Lake Baikal divergence between related species was between 0.7 and 3.8% (Slobodyanyuk et al 1995), which is also in the same range as in the altisambesi/ devosi/pongolensis species pairs. Distances between well established and unrelated genera, e.g.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In cottoid fish of Lake Baikal divergence between related species was between 0.7 and 3.8% (Slobodyanyuk et al 1995), which is also in the same range as in the altisambesi/ devosi/pongolensis species pairs. Distances between well established and unrelated genera, e.g.…”
Section: Discussionmentioning
confidence: 54%
“…In mammals a crude molecular clock equates 2% nucleotide differences with one million years divergence time (Brown et al 1979;Wilson et al 1987). It has been suggested that the molecular clock shows an even slower rate in fishes than in mammals (Cantatore et al 1994;Slobodyanyuk et al 1995). Even if this calibration is very crude it suggests that the taxa within the Macrolepidotus complex that differ by genetic distances between 1.5 and 8.5% must have separated more than one to four million years ago which would be long enough to develop into separate species.…”
Section: Discussionmentioning
confidence: 99%
“…Irwin et al (1991) have analyzed nucleotide sequences of cytochrome b genes of more than 20 mammals. Slobodyanyuk et al (1995) found that the evolution rates determined by Brown et al (1979) and Irwin et al (1991) were very similar (2.1% per million yr). Neighbor Joining is a distance matrix method producing an unrooted tree without the assumption of a clock.…”
Section: Resultsmentioning
confidence: 88%
“…Species numbers and speciation rates in fishes of other lakes of comparable age and in lineages related to those in Lake Victoria but from older lakes. Note that the negative relationship between age of lake and speciation interval is a general trend (McCune 1997 Strecker et al (1996); Laurentian Great lakes: Smith & Todd (1984); lakes on Texada Island and Vancouver Island: Taylor et al (1997), Taylor & McPhail (1999); single species lakes on the Queen Charlottes: Reimchen et al (1985); lakes in East Canada and Maine: Lu et al (2001); lakes in Alaska: Bernatchez et al (1996); lakes in East Canada and Maine: Taylor & Bentzen (1993); Lake Bunnersjoarna/Sweden: Ryman et al (1979), Schluter (1996); Lake Thingvallavatn/Island: Skulason & Smith (1995), Skulason et al (1999); Norway and Scotland: Hindar et al (1986), Hartley et al (1992); Sweden: Svedaeng (1990); Lake Titicaca: Parker in McCune (1997); Lake Edward: Greenwood (1973Greenwood ( , 1994; Lake Lanao: Kornfield & Carpenter (1984); Lake Malawi: Sodsuk et al (1995); Lake Barombi Mbo: Schliewen et al (1994); Lake Malawi: Lowe-McConnell (1987), Agnese & Teugels (2001); Lake Tana: Nagelkerke et al (1995); Lake Baikal: Slobodyanyuk et al (1995)). …”
Section: Discussionmentioning
confidence: 99%